Pemeliharaan Alat Keselamatan Kapal Rakit Penolong pada Kapal TB. Sea Win I oleh PT. Putra Samudera Inti Batam - Yafaeli Hulu; Dirhamsyah Dirhamsyah; Eka Fransiska (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
One of the key elements in ensuring this safety is the readiness and seaworthiness of the ship’s safety equipment, particularly the life raft or rescue raft. The life raft functions as an emergency evacuation device for the crew in the event of dangerous situations such as fire, flooding, or the ship sinking.To ensure that this equipment is always in ready-to-use condition, regular maintenance and inspection processes are required, carried out in accordance with international maritime safety standards.This study aims to examine the maintenance process of the life raft on the TB. Sea Win I vessel, as well as evaluate its compliance with applicable safety standards. The research method used is a descriptive qualitative approach, with data collection techniques including direct observation of the life raft unit, interviews with company management, and documentation of maintenance reports, function test reports, and reinspection certificates.The research results indicate that the life raft maintenance process is carried out systematically and in accordance with the provisions of the International Maritime Organization (IMO) and the Safety of Life at Sea (SOLAS) regulations, specifically Chapter III Regulation 20. Maintenance includes air pressure testing of the inflation cylinder, physical inspection of the raft, checking the emergency equipment inside the life raft such as flares, food supplies, life buoys, and navigational aids, as well as replacing components that have passed their expiration dates.This process is also documented officially through inspection reports and reinspection certificates issued by classification societies or authorized agencies. With regular and professional maintenance, the condition of the life raft on the TB. Sea Win I vessel can be ensured to remain in a ready-to-use state and comply with both national and international maritime safety standards.